2020
DOI: 10.1182/bloodadvances.2019000767
|View full text |Cite
|
Sign up to set email alerts
|

Loncastuximab tesirine, an anti-CD19 antibody-drug conjugate, in relapsed/refractory B-cell acute lymphoblastic leukemia

Abstract: Relapsed or refractory (R/R) B-cell acute lymphoblastic leukemia (B-ALL) remains a therapeutic challenge. Loncastuximab tesirine is an antibody-drug conjugate against CD19, an antigen expressed in many B-cell malignancies. This open-label, single-arm, dose-escalation, dose-expansion study assessed the safety, tolerability, pharmacokinetics (PKs), immunogenicity, and preliminary clinical activity of loncastuximab tesirine in adults with R/R B-ALL. A total of 35 patients were enrolled, with a median age of 55 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Interestingly, recent pre-clinical studies have demonstrated that fractionated dosing of PBD-containing ADCs mitigates side effects and maintains effectiveness [ 44 ]. Although the ABBV-321 recommended clinical dosing regimen remains to be established, previous clinical testing of other PBD-loaded ADCs indicates that clinical doses have been much lower than used here, and or at much longer intervals for a very limited number of cycles [ 45 47 ]. Clinical dosing, safety, and tolerability will be ultimately informed by results from an ongoing phase I clinical trial investigating ABBV-321 in EGFR-overexpressing solid tumors (NCT#03234712).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent pre-clinical studies have demonstrated that fractionated dosing of PBD-containing ADCs mitigates side effects and maintains effectiveness [ 44 ]. Although the ABBV-321 recommended clinical dosing regimen remains to be established, previous clinical testing of other PBD-loaded ADCs indicates that clinical doses have been much lower than used here, and or at much longer intervals for a very limited number of cycles [ 45 47 ]. Clinical dosing, safety, and tolerability will be ultimately informed by results from an ongoing phase I clinical trial investigating ABBV-321 in EGFR-overexpressing solid tumors (NCT#03234712).…”
Section: Discussionmentioning
confidence: 99%
“…Loncastuximab tesirine showed only modest efficacy in B-cell acute lymphoblastic leukaemia [52]. In a phase 1 study in adults with relapsed or refractory disease, a total of 35 patients were enrolled with a median age of 55 and a median of three prior therapies.…”
Section: Loncastuximab Tesirinementioning
confidence: 99%
“…While our work focused on the reduction of toxicity for CAR-based therapies, other antibody-based drug modalities have also been associated with significant toxicities that could be reduced through the use of conditional antibodies. For example, CRS has been associated with T cell-redirecting bispecific antibodies 42 , 43 , and tumor lysis syndrome has been associated with antibody–drug conjugates 44 , 45 , both of which are especially pronounced in patients with high tumor burden. Autoimmune adverse events have been associated with monoclonal antibody-based immune checkpoint inhibitors that target PD-1 and CTLA-4 46 .…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated how these antibodies can be used to generate conditional CAR T cells with target-specific cytotoxicity whose activity can be reversibly attenuated by the addition of a small molecule to potentially mitigate therapy-associated toxicities. In addition to CAR T cells, these unique scaffolds could be applied to a broad range of antibody-based therapeutics for the development of safer therapeutics including, bispecific antibodies 43 , antibody–drug conjugates 44 , 45 , and antibody-based immune-modulatory agents 46 , which are often hindered by a variety of associated adverse effects. Endowing exogenous control over antibody-based therapeutics would dramatically enhance their therapeutic index, thereby increasing their therapeutic value in tackling difficult-to-treat diseases.…”
Section: Discussionmentioning
confidence: 99%